PENGEMBANGAN PENDIDIKAN MORAL KEPADA GENERASI ALPHA DI MTS DARUL MUTTAHIDIN SEBAGAI BENTUK PENGAMALAN PANCASILA KE 2 (KEMANUSIAAN YANG ADIL DAN BERADAB) - Baiq Intan Setiawati Rinjani; Baiq Yani Rosanti; Ida Sugiastuti; Aqilla Deani Alfarosa; Baiq Syiva Hulida Aulia; Muh. Zubair (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this research is to determine the development of moral education in the Alpha generation in Beraim village, the impact of moral education on the Alpha generation, efforts made to implement moral education as a form of practicing the second principle. This type of research uses qualitative research with a descriptive approach and literature study. This method can describe the actual situation at the time of the research through data collection which is then interpreted to obtain data to be analyzed. Data collection techniques include observation, interviews and literature study and documentation. Based on the results of this research, it can be concluded that: a). The development of moral education in the Alpha generation at MTS Darul Muttahudin is quite good and good. b). The impact of Moral education on the Alpha Generation can increase social awareness, develop interpersonal abilities, train emotional intelligence, strengthen cultural identity, reduce dependence on technology, and build value-based character. c). Efforts are made to implement moral education as a form of practicing the second principle by integrating moral education into the curriculum, encouraging the practice of empathy and tolerance, implementing values in schools, building role models for teachers and parents, and we carry out evaluation and reflection.